Perceived strengths and weaknesses of Solidbank Corporation's staff job rotation program - Azhairie, Manda R. (Animo Repository, 1997)
The idea of making a job rotation intervention was based on the expanding business climate of the various Philippine business industries. This practice was first widely used by the Japanese businessmen here in the Philippines until it branched out on its own to different companies with different cultures. Its usefulness has gained a wide acceptance in the banking industry, whether it be local or foreign. Future bankers, needless to say, are trained in this art form of General Management. Going into the investigative department, the subject matter was disected into three vital parts. First statement of the problem was, "What is the profileof Universal Processors who participated in the study?" Secondly, "What are the strengths and weaknesses of the job rotation program perceived bythe Universal Processors?" Thirdly, "Are there differences and similarities on the perceived strengths and weaknesses according gender and length of service?" The study made use of the researcher's adopted survey questionnaire by employing 28 permanent employment status Universal Processors as respondents. Out of the 28 respondents, only 23 people returned the survey questionnaire on time, thus giving the sudy an 82.14% response rate. Survey results were basically tabulation of frequencies, combined SA+A and SD+D percentage scores and weighted mean computations. The results revealed that 10 out of 11 factors withmean scores ranging from 3.5999 to 4.5 acted as the job rotation program's strengths. Meaning, these factors became more of strengths rather than weaknesses because they appeared to be favorable to the respondents. On the other hand and coming in last in the survey, pay was the only factor that did not receive that much vote of confidence from the respondents. Hence, this was perceived as a weakness. As an inference by the researcher, this issue may not be true due to the fact that the problem on salaries and benefits may have existed even before the program was established, or pay at the same level as that of the Universal Processors, is uniform to all staff level employees of Solidbank or any local bank in the Philippines.For a big company like Solidbank, effective management of their job rotation program entails a lot of cost in terms of implementation and maintaining more than a hundred Universal Processors strategically assigned across the Philippine archipelago. In totality, the current impression is that factors such as opportunity for personal growth, job security, responsibility, relations with others, promotion opportunities, recognition, quality of supervision, company policies and physical working conditions is perceived to be strengths of the program, while pay is a weakness.